DEVELOPMENT OF LUDO BASED LEARNING MEDIA WITH THE HOBBY THEME FOR GERMAN SPEAKING SKILLS OF STUDENTS AT STATE SENIOR HIGH SCHOOL 1 DRIYOREJO - Ismana, Mochammad Bagus; Ari Pujosusanto (LATERNE, 2026)
This study aims to develop a game-based learning medium in the form of a Ludo game with the Hobby theme to support the learning of German speaking skills for Phase F students (Grade XI) at SMAN 1 Driyorejo. The background of this research is based on students’ low motivation and confidence in speaking German, as well as the limited availability of interactive learning media. The development model used refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation); however, this study was conducted only up to three stages, namely Analysis, Design, and Development. The analysis stage was carried out through interviews and observations during the PLP activities to identify learning needs, students’ speaking skill problems, and teachers’ needs for innovative and engaging learning media. The design stage included the preparation of the media design in the form of a Ludo game along with its supporting components, such as the game board, dice, player tokens, dialogue cards, and game rules based on the Hobby theme. The development stage resulted in a Ludo learning medium developed according to the design and subsequently validated by material experts and media experts using a Likert scale assessment sheet. The validation results indicate that the Ludo learning media obtained a feasibility percentage of 80% from material experts (feasible category, no revision required) and 92% from media experts (very feasible category, no revision required). Based on these findings, the Hobby-themed Ludo media is considered feasible to be used as an innovative learning medium to support German speaking skills. This product is expected to help create a more interactive and enjoyable learning environment and to increase students’ confidence in using spoken German in the classroom.